2021
DOI: 10.1002/lno.11903
|View full text |Cite
|
Sign up to set email alerts
|

Elevated pCO2 enhances under light but reduces in darkness the growth rate of a diatom, with implications for the fate of phytoplankton below the photic zone

Abstract: Experimentally elevated pCO2 and the associated pH drop are known to differentially affect many aspects of the physiology of diatoms under different environmental conditions or in different regions. However, contrasting responses to elevated pCO2 in the dark and light periods of a diel cycle have not been documented. By growing the model diatom Phaeodactylum tricornutum under 3 light levels and 2 different CO2 concentrations, we found that the elevated pCO2/pH drop projected for future ocean acidification redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…On the contrary, decreased O 2 availability may benefit phytoplankton by slowing down the consumption of intracellular energy reserves. On the other hand, it is generally understood that the acidification associated with elevated pCO 2 increases the energy demands to drive H + extrusion (Taylor et al, 2012), which has been experimentally shown in diatoms (Wu et al, 2010;Goldman et al, 2017;Qu et al, 2021). Consequently, interactive effects of DeO 2 and acidification are expected, and we hypothesize that the resistance of diatoms to concurrent acid stress with increased pCO 2 may be affected by decreased pO 2 , since the availability of the latter impacts respiratory energy generation.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…On the contrary, decreased O 2 availability may benefit phytoplankton by slowing down the consumption of intracellular energy reserves. On the other hand, it is generally understood that the acidification associated with elevated pCO 2 increases the energy demands to drive H + extrusion (Taylor et al, 2012), which has been experimentally shown in diatoms (Wu et al, 2010;Goldman et al, 2017;Qu et al, 2021). Consequently, interactive effects of DeO 2 and acidification are expected, and we hypothesize that the resistance of diatoms to concurrent acid stress with increased pCO 2 may be affected by decreased pO 2 , since the availability of the latter impacts respiratory energy generation.…”
Section: Introductionmentioning
confidence: 77%
“…The reduced O 2 availability aided in such adjustment. On the other hand, elevated pCO 2 associated with the acidic stress is known to enhance respiration rate of diatoms to accommodate the increased energy demands involved in maintaining intracellular pH homeostasis (Wu et al, 2010;Goldman et al, 2017;Qu et al, 2021;Gao et al, 2022). However, a recent study suggests that the increased respiration may not be sufficient to counteract the negative effects induced by acidic stress in darkness, as the cell growth rate of the diatom P. tricornutum decreased in a 48-hour period of complete darkness (Qu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the energy saved from downregulation of CMMs under HC was not enough to bring significant increase of net photosynthesis and growth rate ( Luo et al, 2019 ). Considering that phytoplankton can benefit from the elevated p CO 2 under light but suffer from the acidic stress in darkness, resulting in daytime enhanced and nighttime suppressed growth rates ( Qu et al, 2021 ), the net effects of the HC treatment on growth should be holistically considered for the diel cycle and availability of nutrients ( Table 2 ). We suggest that extra energy required to cope with the acidic stress under HC could be provided via increased dark respiration ( Figure 2 ), compensating for the insufficient energy supply from the downregulation of CCMs in Trichodesmium cells grown under HC.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of ocean acidification depend on the balance between the positive impact of increased CO 2 levels and the negative impact of reduced pH [22,46]. Moreover, the OA effect would also be influenced by other environmental stressors.…”
Section: Discussionmentioning
confidence: 99%